Cercospora Leaf Spot - Monica L. Elliott; Philip F. Harmon (EDIS)
Cercospora leaf spot is a fungal disease of St. Augustinegrass observed during periods of frequent rainfall. This revised 2-page fact sheet was written by M. L. Elliott and P. F. Harmon, and published by the UF Department of Plant Pathology, February 2011.